A Systematic Review of Human Capital in the Digital Economy - Franciskus Antonius Alijoyo; Muhammad Juliansyah Putra; Margaretha Banowati Talim; Endang Fatmawati; B.M.A.S. Anaconda Bangkara (Institut Bisnis dan Informatika Kesatuan, 2026)
The rapid expansion of the digital economy has transformed global production systems, labor markets, trade patterns, and governance structures. In this evolving environment, human capital has emerged as a key determinant of long-term economic competitiveness and resilience. Although studies on digital transformation and workforce development have proliferated, the existing literature remains fragmented across disciplines and geographic contexts. This study aims to conduct a systematic literature review that examines the macroeconomic relationship between human capital and the digital economy. Using the PRISMA framework, 852 records from the Scopus database were screened, yielding 40 studies included in the final synthesis. The analysis identified five dominant research themes: digital-driven economic growth, workforce transformation, digital governance and trade competitiveness, economic resilience, and sectoral digital transformation. The findings consistently demonstrate that digital infrastructure alone is insufficient to generate sustainable economic growth. Instead, outcomes depend heavily on the quality, adaptability, and innovative capacity of human capital. Human capital serves not only as a factor of production but also as a mediator and moderator that shapes the performance of the digital economy by enhancing institutional adaptability, reducing structural constraints, and supporting economic modernization.